2011
DOI: 10.3390/polym3010527
|View full text |Cite
|
Sign up to set email alerts
|

A 3D Electroactive Polypyrrole-Collagen Fibrous Scaffold for Tissue Engineering

Abstract: Fibers that can provide topographical, biochemical and electrical cues would be attractive for directing the differentiation of stem cells into electro-responsive cells such as neuronal or muscular cells. Here we report on the fabrication of polypyrrole-incorporated collagen-based fibers via interfacial polyelectrolyte complexation (IPC). The mean ultimate tensile strength of the fibers is 304.0 ± 61.0 MPa and the Young's Modulus is 10.4 ± 4.3 GPa. Human bone marrow-derived mesenchymal stem cells (hMSCs) are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 34 publications
0
47
0
Order By: Relevance
“…β‐tubulin III and nestin, which are cytoskeleton proteins, are the main marker of neural stem cells (NSCs) and neurons . Researchers found that neural gene markers including β‐tubulin and nestin had significant increases after the human bone marrow MSCs were cultivated on polypyrrole‐incorporated collagen fibrous scaffold and stimulated with 1.2‐V voltage, 200‐Hz frequency with 5‐ms pulse duration . In this study, the low‐level expression of GFAP (major intermediate filament proteins of mature astrocytes) was reported after electrical stimulus in both AC (EFs).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…β‐tubulin III and nestin, which are cytoskeleton proteins, are the main marker of neural stem cells (NSCs) and neurons . Researchers found that neural gene markers including β‐tubulin and nestin had significant increases after the human bone marrow MSCs were cultivated on polypyrrole‐incorporated collagen fibrous scaffold and stimulated with 1.2‐V voltage, 200‐Hz frequency with 5‐ms pulse duration . In this study, the low‐level expression of GFAP (major intermediate filament proteins of mature astrocytes) was reported after electrical stimulus in both AC (EFs).…”
Section: Discussionmentioning
confidence: 75%
“…In the same study, researchers used an electrical stimulus with the 0.1‐Hz frequency which expressed the decreases of cell viability of this current . In another study, MSCs were stimulated on a PPy (Poly‐pyrrole) based substrate and it was reported that on the 5th day the cell proliferation increased, while on the 10th day it decreased compared to the nonstimulated group . In the present study, CJMSCs were stimulated on SF‐rGo conductive scaffold and the cell proliferation was examined on the third, fifth and seventh days after electrical stimulation (0.1 and 100 Hz).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In spite of this, the number of studies devoted to fabricate bioactive platforms for tissue engineering based on the combination of collagen with CPs is, unfortunately, very scarce yet. [19][20][21][22][23] Thus, such studies are limited to the encapsulation of polypyrrole into collagen fibers, 19 the preparation of patterned platforms by inkjet printing polypyrrole and collagen lines on polyarate films, 20 the dispersion of polyaniline nanofibers in a collagen matrix, 21 and the preparation of CP-collagen composites using polypyrrole and polythiophene derivatives. [21][22][23] Poly (3,4-ethylenedioxythiophene), hereafter abbreviated PEDOT (Scheme 1), is one of the most important CPs due to its high electrical conductivity (up to 500 S/cm), excellent electrochemical properties and biocompatibility, and fast doping-dedoping processes.…”
Section: Introductionmentioning
confidence: 99%
“…The natural polyelectrolytes chitosan and alginate were used due to its high charge density and similarity to various ECM carbohydrates found in animal tissues. Yet methylated collagen and terpolymer 8,19 or chitin and alginate 20 may also be used for IPC fiber formation to varying effects.…”
mentioning
confidence: 99%